Allelopathy: an eco-friendly approach to control palmer amaranth using allelopathic sweetpotato - Singh, Varsha; Segbefia, Worlanyo; Fuller, Mary Gracen; Shankle, Mark W.; Morris, Callie J.; Meyers, Stephen L.; Tseng, Te-Ming (Frontiers in Agronomy, 2022)
Mississippi state is the second-largest sweet potato producer after North Carolina in the US. However, weeds, especially Palmer amaranth, cause a reduction in the yield and quality of sweet potato. The present study was conducted in the greenhouse under controlled conditions to uncover the allelopathic effects of different sweet potato varieties on the growth of Palmer amaranth. The experiment was carried out in a stair-step setup. There were two columns for each sweet potato variety - the treatment column and the control column, and one weed control column as well. This screening and ANOVA results showed that the variation for the traits recorded was significant starting from 3 WAT. At 3 WAT, only three varieties, i.e., Morado (75%), Bayou belle (62%), and Vardaman (61%), reduced the Palmer amaranth height by >60% compared to the control. While, at 5 WAT, four varieties, i.e., 529 (93%), Morado (93%), Heartogold (85%), and Centennial (81%), reduced the weed height by more than 80%. Hatteras, Centennial, and 529 reduced the chlorophyll content of Palmer amaranth by >50%. Though the reduction in the biomass of Palmer amaranth did not vary significantly among other varieties, the reduction by Beauregard was lesser than other varieties under study. Cluster analysis of sweet potato varieties using Ward’s method also grouped the allelopathic and non allelopathic varieties separately. Identification of sweet potato varieties responsible for allelopathic effect will give an entirely new direction to weed management in crop plants. The availability of allelopathic sweet potato will be especially beneficial to organic growers by increasing crop production and reducing the dependency on chemical herbicides.